Mechanical properties of ultrafine-grained AlZnMg(Cu)-alloys AA7020 and AA7075 processed by accumulative roll bonding - Ruppert, Mathis; Strebl, Michael; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2015)
Ultrafine-grained AA7020 (AlZnMg) and AA7075 (AlZnMgCu) were produced by accumulative roll bonding (ARB) with up to 6 cycles. Different pre-heating treatments and their effect on the mechanical performance of the materials were investigated by means of hardness measurements and uniaxial tensile testing. It was found for AA7020 that by pre-heating at 230 degrees C for 2.5 min prior to each rolling step, an UTS of 550 MPa can be achieved, which is 51 % higher compared to the peak-aged T6 reference. For AA7075, pre-heating at 280 degrees C for 2.5 min leads to a very high UTS of 720 MPa after four ARB passes. A negative strain rate sensitivity was found for both alloys, which shifts toward zero with increasing number of ARB cycles. Post-ARB heat treatment was performed in order to overcome the reduced ductility after ARB. This leads to an enhanced strain hardening capacity after 4 cycles, resulting in an increase of the uniform elongation from 1.4 to 2.0 % for AA7020 and from 0.9 to 2.1 % for AA7075.